Analysis of accelerations in turbulence based on generalized statistics - Arimitsu, T.; Arimitsu, N. (Condensed Matter Physics, 2003)
An analytical expression of probability density function (PDF) of accelerations
in turbulence is derived with the help of the statistics based on generalized
entropy (the Tsallis entropy or the Ren´ yi entropy). It is revealed that
the derived PDF explains the one obtained by Bodenschatz et al. in the
measurement of fluid particle accelerations in fully developed turbulence
at Rλ = 970 . За допомогою статистики, яка базується на узагальненій ентропії (ентропії Цалліса чи ентропії Рені) виведено аналітичний вираз для функції густини ймовірності прискорень при турбулентності. Виявлено, що дана функція пояснює результат, отриманий Боденшацом та ін. при вимірюванні прискорень частинок флюїду за умов повністю розвинутої турбулентності при Rλ = 970 .